2021
DOI: 10.1371/journal.pone.0259433
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different Kinesio tape tensions on experimentally-induced thermal and muscle pain in healthy adults

Abstract: Athletes and rehabilitation specialists have used Kinesio tape (KT) to help alleviate pain symptoms. Currently, no clear mechanism exists as to why pain is relieved with the use of KT and whether the pain relieving effect is simply a placebo effect. Additionally, the most effective taping parameters (tension of tape) for pain reduction remain unknown. We used quantitative sensory testing to address these key gaps in the KT and pain literature. Using a repeated-measures laboratory design, we examined whether KT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Combining our results with those of other studies, it appears that the specific taping technique and direction of tape application are of little significance. Furthermore, with no consensus on how much tape tension is most beneficial ( 44 , 45 ), the patient has freedom to experiment with different configurations and varying amounts of tension that may yield the optimal short-term benefit with little skin irritation.…”
Section: Discussionmentioning
confidence: 99%
“…Combining our results with those of other studies, it appears that the specific taping technique and direction of tape application are of little significance. Furthermore, with no consensus on how much tape tension is most beneficial ( 44 , 45 ), the patient has freedom to experiment with different configurations and varying amounts of tension that may yield the optimal short-term benefit with little skin irritation.…”
Section: Discussionmentioning
confidence: 99%
“…KT is being increasingly used in clinical practice, and several studies have reported KT as a therapeutic intervention that may improve outcomes with lower costs. Some studies have reported that KT application may improve muscle strength and motor function and recommend the use of KT as a treatment resource and even as a tool to assist in injury prevention [ 20 , 28 , 31 39 ]. These studies presented that the stretch applied on the tape provides a pre-pulling force on the skin, stimulating cutaneous mechanoreceptors and altering motor neuron activation, thereby improving communication with mechanoreceptors and increasing the number of motor units recruited.…”
Section: Discussionmentioning
confidence: 99%
“…14,17 Disamping itu terdapat penelitian penggunaan kinesio tape tidak berpengaruh secara signifikan terlebih pada atlet tanpa permasalah muskuloskeletal. 18,19 Tujuan penelitian ini adalah untuk mengetahui efektivitas dari penggunaan kinesio tape dalam stabilitas knee saat melakukan drop landing basket pada pemain sehat. Diharapkan hasil penelitian ini dapat memberikan informasi yang dapat dijadikan landasan dalam pencegahan risiko cedera lutuh.…”
Section: Pendahuluanunclassified
“…Beberapa literatur lain menyebutkan bahwa penggunaan kinesio tape tidak memberikan pengaruh secara signifikan terlebih pada atlet tanpa permasalahan cedera muskuloskeletal sebelumnya. 18,19…”
Section: Hasilunclassified
See 1 more Smart Citation